De favela a bairro educador: protagonismo comunitário em Heliópolis - Santis, Marília de (2014)
This master's degree dissertation studies the mechanisms of community participation that settled in the region of Heliopolis for the effectiveness of an educational project called Educator District, which is under implementation. The research was limited to educational and cultural facilities located in the locality and to the collective of associations, gathered into a single community institution that represents the community of the region. This is an investigation of a qualitative approach that drew upon successive stages of research and different methodologies, techniques and procedures: the documentary research raised historical constitution of the favela (slum), based on government texts and protocols of meetings of the Community institution; the systematic observation, using observation script and logbook was used for recognition of the field and of the universe of the study; the field research drew on participant observation in meetings and was followed by interviews with residents and community leaders responsible for implementing this public policy in education. Within the meaning of the various actors interviewed, we sought to understand the pedagogical concepts that were and is based the policy implementation of the project. In this step, we seek to unravel the ways in which occurs the participation of organized popular movements in the region, understood as social leadership that arises in partnership with the government for the enforcement of a public policy.